Dampak Sosial Ekonomi Peternakan Ayam Kampung Berskala Mikro Di Desa Payaman, Nganjuk - Damar Tyas Pangestu; Siti Azizah (FKIP, Universitas Palangka Raya, 2022)
This research was conducted at a local micro-scale, Mr. Junaidi's local chicken farm, Payaman Village, Payaman Village, Nganjuk Regency, from November 20 to February 18, 2022. The purpose of the study was to determine the community's response to the existence of free-range chicken farming and determine the socio-economic impact on the community around the farm. The research was conducted using qualitative methods. It collects data using direct interviews with people who live around the farm using a questionnaire and sampling technique using purposive sampling. The results showed that the community's response around the farm did not object to the existence of a community-scale free-range chicken farm as long as it did not interfere with community activities and did not cause excessive negative impacts. The social impacts that arise from the existence of a community-owned free-range chicken farm in Payaman Village consist of positive impacts such as creating new business opportunities, employment opportunities, and motivating the community. The negative impacts that arise are environmental pollution, the emergence of conflict, and competition. The economic impacts felt by the community include the positive impact in the form of additional income from a side business from selling karak nasi (dried rice) for chicken feed, opening rice stalls, and basic food shops around the coop. The cage needs attention to avoid wild animals and predators such as snakes, monitor lizards, and civets that endanger livestock and residents. Reducing odors and diseases as environmental pollution around residential areas by giving fly repellent and cleaning chicken manure is needed. The waste treatment process is also very much required; this aims to reduce disease risk and reduce environmental pollution for farming sustainability